A video intervention to improve patient understanding of tumor genomic testing in patients with cancer - Deloris J. Veney; Lai Y. Wei; Amanda E. Toland; Carolyn J. Presley; Heather L. Hampel; Tasleem J. Padamsee; Clara N. Lee; William J. Irvin Jr; Michael J. Bishop; James J. Kim; Shelly R. Hovick; Leigha A. Senter; et al. (Cancer Medicine)
Abstract Introduction Tumor genomic testing (TGT) is standard‐of‐care for most patients with advanced/metastatic cancer. Despite established guidelines, patient education prior to TGT is frequently omitted. The purpose of this study was to evaluate the impact of a concise 4 min video for patient education prior to TGT. Methods Based on a quality improvement cycle, an animated video was created to be applicable to any cancer type, incorporating culturally diverse images, available in English and Spanish. Patients undergoing standard‐of‐care TGT were enrolled at a tertiary academic institution and completed survey instruments prior to video viewing (T1) and immediately post‐viewing (T2). Instruments included: (1) 10‐question objective genomic knowledge; (2) 10‐question video message‐specific knowledge; (3) 11‐question Trust in Provider; (4) attitudes regarding TGT. Results A total of 150 participants were enrolled. For the primary objective, there was a significant increase in video message‐specific knowledge (median 10 point increase; p < 0.0001) with no significant change in genomic knowledge/understanding (p = 0.89) or trust in physician/provider (p = 0.59). Results for five questions significantly improved, including the likelihood of TGT impact on treatment decision, incidental germline findings, and cost of testing. Improvement in video message‐specific knowledge was consistent across demographic groups, including age, income, and education. Conclusions A concise, 3–4 min, broadly applicable video incorporating culturally diverse images administered prior to TGT significantly improved video message‐specific knowledge across all demographic groups. This resource is publicly available at http://www.tumor‐testing.com, with a goal to efficiently educate and empower patients regarding TGT while addressing guidelines within the flow of clinical practice.